1987
DOI: 10.1523/jneurosci.07-03-00662.1987
|View full text |Cite
|
Sign up to set email alerts
|

Interruption of the connections of the mammillary bodies protects against generalized pentylenetetrazol seizures in guinea pigs

Abstract: Electrolytic lesions in the anterior and mid-diencephalon and ventral midbrain in guinea pigs were produced to examine the effects of interruption of the fornix (FX), mammillothalamic tracts (MT), and mammillary peduncles (MP), respectively, on the expression of pentylenetetrazol (PTZ) seizures. As a group, all mid-diencephalic lesioned animals had some degree of protection from the electroencephalographic and behavioral convulsant and lethal effects of the drug. Through a composite volume analysis of protecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0
3

Year Published

1987
1987
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(25 citation statements)
references
References 37 publications
(44 reference statements)
1
21
0
3
Order By: Relevance
“…Experiments supporting the hypothesis of AN mediation of convulsive activity include selective uptake of radioactively labeled glucose by AN during a threshold seizure state, as well as site-specific sensitivity to a variety of agents known to block PTZ seizure expression (12,13). Additional confirmation of the role of the AN in the expression of these seizures came from lesioning of afferent tracts synapsing on AN, and the raising of seizure threshold by localized high-frequency electrical stimulation (14,15). Such evidence has led to pilot clinical trials of AN stimulation for refractory seizures, and recently a National Institutes of Health (NIH)-sponsored clinical trial (RO1NS39344-01).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments supporting the hypothesis of AN mediation of convulsive activity include selective uptake of radioactively labeled glucose by AN during a threshold seizure state, as well as site-specific sensitivity to a variety of agents known to block PTZ seizure expression (12,13). Additional confirmation of the role of the AN in the expression of these seizures came from lesioning of afferent tracts synapsing on AN, and the raising of seizure threshold by localized high-frequency electrical stimulation (14,15). Such evidence has led to pilot clinical trials of AN stimulation for refractory seizures, and recently a National Institutes of Health (NIH)-sponsored clinical trial (RO1NS39344-01).…”
mentioning
confidence: 99%
“…Previously we established that the thalamic anterior nuclear complex (AN), a thalamic element of the limbic system, is an important gating center for the propagation of pentylenetetrazol (PTZ) seizure activity (11)(12)(13)(14)(15). Experiments supporting the hypothesis of AN mediation of convulsive activity include selective uptake of radioactively labeled glucose by AN during a threshold seizure state, as well as site-specific sensitivity to a variety of agents known to block PTZ seizure expression (12,13).…”
mentioning
confidence: 99%
“…Это привело к дальнейшему повышению ин-тереса исследователей к данной анатомической об-ласти [9]. В 1987 г. M. Mirski и J. Ferrendelli [10] опублико-вали результаты экспериментальной работы, указы-вающие на антиэпилептогенное действие электро-литического разрушения различных структур круга Пейпеца, включая форникс, мамиллоталамический тракт и мамиллярные ножки, на судорожные при-ступы у морских свинок, вызванные введением пен-тилентетразола. Локальные микроинъекции в пе-редние таламические ядра аналога γ-амино масляной кислоты мусцимола или γ-винил-γ-аминомасляной кислоты (необратимого ингибитора трансаминазы γ-аминомасляной кислоты) в исследованиях также приводили к значительному повышению резистент-ности к пентилентетразол-индуцированным судо-рогам [11,12].…”
Section: Discussionunclassified
“…Studies by Hamani et al, have tested the efficacy of ATN-DBS in a pilocarpine induced epilepsy model and found that bilateral ATN stimulation prolonged latencies for pilocarpine-induced seizures and status epilepticus 24 . Furthermore, high frequency stimulation of the ATN was found to reduce seizure frequency in a pentylenetetrazol (PTZ) model of epilepsy 25,[27][28][29] . Lee et al, have reported a mean reduction in seizure frequency by about 75% upon chronic deep brain stimulation of the ATN in treating refractory partial epilepsy 30 .…”
Section: Introductionmentioning
confidence: 99%